Penerapan Risk Management Operational dan Pengaruhnya terhadap Mutu Pelayanan Di PT.UOB Property Jakarta - Chaerudin, Iman (Journal of Economics & Business UBS, 2020)
Implementation of operational risk management on the object property is very important in order to improve the quality of service so that the tenants more comfortable so that they continue to rent the premises. There are four divisions that are in direct contact with the occupants of the building that affect the quality of service that is division Tenant Relations, Engineering, Housekeeping and Security, therefore researchers interested in conducting research with the aim of knowing the operational risks of the building on the division Tenant Relations, Engineering, housekeeping and security and want to know the relationship of the four divisions with the quality of service. This research was conducted in PT.UOB PROPERTY with UOB Plaza building in Jakarta with population of 35 tenants and taken sample 25 respondents by using direct study in field and literature study, while to know the relationship of the four divisions with Spss 24 by using sample random sampling technique with 25 respondents. From the analysis results, there are operational risks with risk classification and low, medium and high impact in the TR (x1), Engineering (x2), Housekeeping (x3) and Security (x4) divisions.The results of the data using Spss 24 generated regression model Y = 0.353x1 + 0.585x2 + 0.567x3 - 0.040x4 - 3.621 and based on F test results that variable div.TR, Eng, HK, and div. Security variables simultaneously affect the variable the quality of the service, or by looking at the computation of F arithmetic with F table, from table F obtained data F table of 2.759, while F arithmetic of 43,070 thus F table (2.759) <F count (43.070) or F count (43.070)> F table (2.759) so that it can be concluded independent variable (X) div TR, Engineering, Housekeeping and Security simultaneously together affect the quality of service (Y), while based on test results t only engineering division (x2) , while for division Tenant relation, Housekeeping and security have no relation with service of quality.